A Suspended Array of Square Patch Metamaterial Absorbers for Terahertz Applications. (2015) - Torun, H.; Sadeghzadeh, S.; Bilgin, H.; Yalcinkaya, A.D.
Abstract: A suspended array of square metallic patches on a thin dielectric layer is introduced as a terahertz absorber. The absorber is fabricated on a metalized substrate and the device exhibits metamaterial behavior at specific frequencies determined by the size of the patches. It is feasible to place patches with different sizes in an array formation for a broadband absorber. Design of the absorber is described using electromagnetic simulations. The absorber structure was fabricated on a silicon wafer and its characteristics were measured using a terahertz time domain spectroscope. The measured data match well the simulations indicating strong absorption peaks in a band of 0.5-2 THz.